2008
DOI: 10.1097/smj.0b013e3181840bc5
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use Among Primary Care Patients in West Texas

Abstract: CAM use is clearly not uncommon among primary care patients in rural areas, with more than half of patients reporting some type of use. This study suggests that further research should elicit opinions on CAM among people who do not regularly access a conventional primary care provider, as well as assess the relationship between CAM and conventional medical treatment in terms of cost and health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Ng and colleagues 34 examined CAM consumption patterns of 453 Hispanic and white psychiatric outpatients in rural California and found significant differences in the use of various CAM products between these 2 ethnic groups: Hispanics were far more likely to consume “natural” or self‐prepared CAM products (or products that require some preparation before consumption), whereas whites used more commercially processed or ready‐to‐use CAM products (preparations in “ready‐to‐use” form). However, a cross‐sectional study of 1,968 patients attending low‐income primary care clinics in rural West Texas found that Hispanics were far less likely to use practitioner‐based CAM than persons of nonHispanic origin 68 …”
Section: Evidence Base For Cam In Rural Health: Current Research and mentioning
confidence: 99%
See 1 more Smart Citation
“…Ng and colleagues 34 examined CAM consumption patterns of 453 Hispanic and white psychiatric outpatients in rural California and found significant differences in the use of various CAM products between these 2 ethnic groups: Hispanics were far more likely to consume “natural” or self‐prepared CAM products (or products that require some preparation before consumption), whereas whites used more commercially processed or ready‐to‐use CAM products (preparations in “ready‐to‐use” form). However, a cross‐sectional study of 1,968 patients attending low‐income primary care clinics in rural West Texas found that Hispanics were far less likely to use practitioner‐based CAM than persons of nonHispanic origin 68 …”
Section: Evidence Base For Cam In Rural Health: Current Research and mentioning
confidence: 99%
“…A qualitative study of naturopaths in rural Australia also found that naturopaths perceived that they were used as primary‐point‐of‐care practitioners more often in rural practices than they were in urban areas 74 . Meanwhile, Zhang and associates’ 68 survey of rural West Texans found that patients who had been able to arrange an appointment for routine care as soon as they wanted were less likely to use CAM than those who had not.…”
Section: Evidence Base For Cam In Rural Health: Current Research and mentioning
confidence: 99%
“…2 However, in rural southern areas, 52.0% of complementary and alternative medicine users and 22.2% of the general population currently sees or has been to a chiropractic physician in the past year. 3 Evidence that up to 70% of US doctors of chiropractic offer care free or at reduced cost to underprivileged patients, 4 underscores the importance of following proper intake procedures, including screening for red flags, because poorer patients who neglect to receive regular medical care are among the highest at-risk population for stroke. 1 Hence, both the highest stroke prevalence and the highest chiropractic use may coexist in the same rural and relatively impoverished southern region of the United States.…”
mentioning
confidence: 99%
“…Many patients seek treatment options, particularly CAM therapies, [5][6][7] that are not currently offered in or through primary care, and they often are reluctant to tell their health care clinicians about their use of these treatments for fear of a negative reaction. [8][9][10][11] A more integrated and inclusive approach to healing that provides a wider range of treatment choices may improve patient satisfaction, decrease costs (by avoiding expensive…”
Section: N the Report Complementary And Alternative Medicine In Thementioning
confidence: 99%